2020
DOI: 10.1016/j.ijsu.2020.05.033
|View full text |Cite
|
Sign up to set email alerts
|

A surgeon’s role in fighting a medical pandemic: Experiences from the unit at the epicentre of COVID-19 in Singapore – A cohort perspective

Abstract: Although Singapore was one of the first countries outside of China to be affected by COVID-19, for the first 2.5 months since its first reported case on January 23, 2020, it remained one of the few nations with successful containment of spread of the pandemic with little mortality and zero intra-hospital transmissions, without instituting a major lockdown of the country. In times of an infectious epidemic where medical subspecialties lead the frontline, a surgeon's role becomes rather vague. However, the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 22 publications
(28 reference statements)
0
13
0
2
Order By: Relevance
“…Support' of the wellbeing of trainees is of crucial importance and cannot be overstated. 14 , 15 There is significant variation in the delivery of wellbeing support throughout the National Health Service, even between departments within the same hospital. Studies have suggested the introduction of a definition of wellbeing, with tangible outcome measures, may be useful in enabling staff to make better use of the wellbeing resources available to them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Support' of the wellbeing of trainees is of crucial importance and cannot be overstated. 14 , 15 There is significant variation in the delivery of wellbeing support throughout the National Health Service, even between departments within the same hospital. Studies have suggested the introduction of a definition of wellbeing, with tangible outcome measures, may be useful in enabling staff to make better use of the wellbeing resources available to them.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons need to be more transparent about their psychological needs, and senior leaders should be encouraging and supportive of this. 14 Structured leadership programmes should be incorporated into surgical training curricula, 23 rather than courses that trainees are expected to attend of their own accord. Shared responsibility to support colleagues and encourage them not to continue working in the face of personal risk as self-less acts is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high infection rate among healthcare workers, the safety of healthcare workers from specialties other than respiratory and infectious diseases has become a widespread concern. Although surgeons have shared their opinions and experiences in the work to combat the COVID‐19 pandemic 6–8 , based on the outcome of a search in PubMed, up to now no published data is able to provide evidence to illuminate whether or not it is safe for medical staff from other specialties to provide support in the work against the COVID‐19 pandemic. In addition, the effectiveness of this kind of support is not yet documented.…”
Section: Introductionmentioning
confidence: 99%
“…The survey was administered to an adult sample of Singapore’s general population during the initial stages of the COVID-19 pandemic. This provided the unique opportunity to capture public opinion during a period of potential physical, psychological, and financial turmoil of an outbreak-turned-pandemic [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%